Analisis Keseimbangan Permintaan dan Penawaran Minyak Goreng Premium Di Kota Semarang - Theo Adrian Healthon; Titik Ekowati; Siswanto Imam Santoso (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Demand and supply play an important role in the formation of price equilibrium in agricultural products such as palm cooking oil. The balance of demand and supply for cooking oil in the market is the result of an agreement between consumers and traders. This equilibrium point will last a long time and become a benchmark for buyers and sellers in determining prices. The study aims to analyze the factors that affect the demand and supply of cooking oil and analyze the equilibrium price of premium cooking oil. The method used in this research is a survey. This research was conducted in December 2022 - January 2023 located in Peterongan, Karimata, Bulu, and Karangayu markets. The location was determined purposively. Sampling using Non Probability Sampling, namely Quota Sampling with 50 respondents per market so that a total of 200 respondents. The data of this study are primary data in the form of interviews with consumers and secondary data for 2017-2021 from the Central Bureau of Statistics. The analysis used in this research is quantitative analysis with multiple linear regression and Cobweb analysis. The results showed that domestic CPO prices, domestic CPO production, supply lag partially had a significant effect on supply while simultaneously the trader level price, substitute price, domestic CPO price, domestic CPO production, and supply lag had a significant effect. Consumer income, population, and demand lag have a partially significant effect on the demand for premium cooking oil while simultaneously consumer-level prices, substitution prices, population, brands, consumer income, and demand lag have a significant effect. The demand and supply equilibrium of premium cooking oil in Semarang City is convergent (close to equilibrium) with the value of b = -0.76 < 1.